The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1977
DOI: 10.1017/s0022112077000780
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear stability of parallel flows with subcritical Reynolds numbers. Part 2. Stability of pipe Poiseuille flow to finite axisymmetric disturbances

Abstract: A theoretical study is presented of the spatial stability of flow in a circular pipe to small but finite axisymmetric disturbances. The disturbance is represented by a Fourier series with respect to time, and the truncated system of equations for the components up to the second-harmonic wave is derived under a rational assumption concerning the magnitudes of the Fourier components. The solution provides a relation between the damping rate and the amplitude of disturbance. Numerical calculations are carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…All these authors used Landau theory. Itoh, how ever, suggested that the application of Landau theory to pipe flow might not be justified since Landau theo ry needs the vicinity of a linear instability [9], Later on Patera and Orszag [10] confirmed Itoh's suggestion by numerical simulations, and so do we: There is no non-linear instability of the kind imagined by Davey and Nguyen. Another interesting approach was the application of non-linear boundary-layer theory by Smith and Bodonyi [11], In contrast to Davey and Nguyen [7], these authors found that the onset of turbulence should be caused by a non-axisymmetric disturbance, and so do we (Sect.…”
Section: Even the Most Ordinary Things Are Not Understoodmentioning
confidence: 77%
See 2 more Smart Citations
“…All these authors used Landau theory. Itoh, how ever, suggested that the application of Landau theory to pipe flow might not be justified since Landau theo ry needs the vicinity of a linear instability [9], Later on Patera and Orszag [10] confirmed Itoh's suggestion by numerical simulations, and so do we: There is no non-linear instability of the kind imagined by Davey and Nguyen. Another interesting approach was the application of non-linear boundary-layer theory by Smith and Bodonyi [11], In contrast to Davey and Nguyen [7], these authors found that the onset of turbulence should be caused by a non-axisymmetric disturbance, and so do we (Sect.…”
Section: Even the Most Ordinary Things Are Not Understoodmentioning
confidence: 77%
“…This is a stringent test since also an analytical formula (A.12) is available for these inte grals. Numerical and analytical results coincide only if the checked functions satisfy at the same time differen tial equation (9) and boundary conditions (5-6).…”
Section: Numerics and Checksmentioning
confidence: 93%
See 1 more Smart Citation
“…This means that in PCF two-dimensional waves with k ≈ 0.13( Re ) 1/2 are the most unstable. Later Davey (1978) found that the results of his paper with Nguyen relating to disturbances in PCF are very close to those which follow from the application to the same problem of another method of the same type proposed by Itoh (1977b). More detailed calculations of the values of A e (k, Re) and E e (k, Re) for numerous values of the arguments (k, Re), also based on a version of the ReynoldsPotter method, were made by Coffee (1977), whose results agree satisfactorily with earlier estimates by Ellingsen et al and Davey and Nguyen.…”
Section: Plane Couette and Circular Poiseuille Flowsmentioning
confidence: 60%
“…The amplitude equation (2.44) is then in fact, when A u, exactly that which can be derived using multiple scale methods (Davey and Nguyen (1971)), although the correctness of such equations is in doubt (Itoh (1977), Davey (1978)). However, it does seem likely that some such unstable solution branch bifurcates from infinity, as is suggested by the work of Rosenblat and Davis (1979) and Smith and Bodonyi (1982).…”
Section: Closure Assumptionsmentioning
confidence: 90%